Behavioural factors as determinants of tax compliance in the COVID-19 era - Shuid, Siti Hawa; Ismail, Norhidayah; Abdul Jabar, Ja’izah; Azis, Saflina (2022)
The term "tax compliance" refers to the process of submitting tax returns and paying taxes in conformity with tax laws. There is uncertainty regarding whether taxpayers will continue to appropriately fulfil their tax obligations in light of the current COVID-19 scenario, particularly during stressful times. Therefore, this study explores the behavioural factors influencing tax compliance among individual taxpayers during a pandemic. There has been discussion of underlying theories that could explain the behavioural aspects of tax compliance. This paper is a conceptual paper. Data will be collected using quantitative data from selected individual taxpayers in Malaysia. A questionnaire survey will be used to collect data from Malaysian taxpayers in order to assess their behaviour towards tax compliance after a crisis. Based on the review of past studies, it was found that attitude, subjective norms, perceived behavioural controls, and moral obligation are the determinant factors of voluntary tax compliance behaviour. Results from this study could have helped tax authorities better understand taxpayer behaviour and develop the appropriate strategies to increase taxpayer compliance with tax laws.